2023
DOI: 10.3343/alm.2023.0187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Genomic Alterations Using Pan-Cancer Cell-Free DNA Next-Generation Sequencing in Patients With Gastric Cancer

Boyeon Kim,
Yoonjung Kim,
Jae Yong Cho
et al.

Abstract: Background: Molecular cancer profiling may lead to appropriate trials for molecularly targeted therapies. Cell-free DNA (cfDNA) is a promising diagnostic and/or prognostic biomarker in gastric cancer (GC). We characterized somatic genomic alterations in cfDNA of patients with GC.Methods: Medical records and cfDNA data of 81 patients diagnosed as having GC were reviewed. Forty-nine and 32 patients were tested using the Oncomine Pan-Cancer Cell-Free Assay on the Ion Torrent platform and AlphaLiquid 100 kit on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Specific to FGF signaling, particularly FGF1-FGFR2, showed significant activation only in tumor samples. Furthermore, FGFR2 overexpression is linked to a poor diagnosis and treatment response [ 33 ], and its rearrangement or fusion is concentrated in intrahepatic cholangiocarcinoma [ 34 , 35 ]. Previous studies have shown that key downstream signaling pathways altered by FGF-FGFR activation are the PI3K-AKT-mTOR pathway [ 36 ], which plays a central role in multiple oncogenic signaling pathways that drive tumorigenesis and progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific to FGF signaling, particularly FGF1-FGFR2, showed significant activation only in tumor samples. Furthermore, FGFR2 overexpression is linked to a poor diagnosis and treatment response [ 33 ], and its rearrangement or fusion is concentrated in intrahepatic cholangiocarcinoma [ 34 , 35 ]. Previous studies have shown that key downstream signaling pathways altered by FGF-FGFR activation are the PI3K-AKT-mTOR pathway [ 36 ], which plays a central role in multiple oncogenic signaling pathways that drive tumorigenesis and progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key advantages of NGS in colorectal cancer is its ability to simultaneously examine multiple genes and genetic mutations within a single test. This high-throughput capability allows for the identification of clinically relevant genetic alterations, such as mutations in KRAS, NRAS, BRAF, and other genes, which are critical for determining treatment options. , The identification of specific mutations or gene expression patterns in the tumor helps clinicians select the most appropriate targeted therapies or immunotherapies, enhancing treatment efficacy, and minimizing potential side effects. NGS also plays a pivotal role in uncovering rare or less common genetic alterations in colorectal cancer.…”
Section: Challenges and Considerations In Precision Medicine Implemen...mentioning
confidence: 99%
“…In an ongoing study, the identification of novel genomic alterations in cfDNA could hold actionable therapeutic interest, such as ERBB2, FGFR2, and TP53 in 4.9%, 6.2%, and 38.3%, respectively. The identification of these mutations could distinguish GC cases from others ( Kim et al, 2024 ). In PDAC patients, the Microsatellite Instability (MSI)-high status is usually assessed for therapy using immune checkpoint inhibitor drugs like pembrolizumab, nivolumab, or those administered with ipilimumab.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%